The pathogenetic role of vitamin D and vitamin D-binding protein in the development of urinary tract infection in children - H.O. Lezhenko; O.Ye. Abaturov; N.A. Zakharchenko (Zaslavsky O.Yu., 2022)
Background. The aim of the research was to study the content of 1,25(OH)2D3 and vitamin D-binding protein (DBP) in the blood serum of children with urinary tract infections, taking into account the clinical form of the disease, and to determine their pathogenetic role in the development of urinary tract infections. Materials and methods. The study groups consisted of 84 children (mean age - 10.0 ± 1.3 years). The main group was divided into subgroups: the first one - 17 children with acute pyelonephritis, the second one - 21 patients with chronic pyelonephritis, the third one - 16 children with acute cystitis, the fourth one - 10 patients with unspecified urinary tract infections. The control group consisted of 20 relatively healthy children. The content of 1,25(OH)2D3 and DBP was investigated by immunoenzymatic analysis. Results. It was found that the development of the inflammatory process in the urinary tract was accompanied by a statistically significant (p < 0.01) decrease in the level of 1,25(OH)2D3 in the blood serum of the children of the main group compared to the controls. The level of 1,25(OH)2D3 in patients of all subgroups was significantly lower than that of the control group (p < 0.01), but there was no statistical difference between them. Serum level of DBP in the main group was statistically significantly (p < 0.05) increased compared to the controls, but we did not find a statistically significant difference between the subgroups studied. Conclusions. The development of an acute inflammatory process in the urinary tract in children occurs against the background of a statistically significant decrease in the blood level of 1,25(OH)2D3 combined with high levels of vitamin D-binding protein. This serves as a pathogenetic basis for the need to develop therapeutic and prophylactic schemes for prescribing vitamin D to children with urinary tract infections.